Magnetic resonance fingerprinting using echo-planar imaging: Joint quantification of T1 and relaxation times - Rieger, Benedikt; Zimmer, Fabian; Zapp, Jascha; Weingärtner, Sebastian; Schad, Lothar R. (Magnetic resonance in medicine, 2017)
Purpose To develop an implementation of the magnetic resonance fingerprinting (MRF) paradigm for quantitative imaging using echo-planar imaging (EPI) for simultaneous assessment of T1 and . Methods The proposed MRF method (MRF-EPI) is based on the acquisition of 160 gradient-spoiled EPI images with rapid, parallel-imaging accelerated, Cartesian readout and a measurement time of 10 s per slice. Contrast variation is induced using an initial inversion pulse, and varying the flip angles, echo times, and repetition times throughout the sequence. Joint quantification of T1 and is performed using dictionary matching with integrated correction. The quantification accuracy of the method was validated in phantom scans and in vivo in 6 healthy subjects. Results Joint T1 and parameter maps acquired with MRF-EPI in phantoms are in good agreement with reference measurements, showing deviations under 5% and 4% for T1 and , respectively. In vivo baseline images were visually free of artifacts. In vivo relaxation times are in good agreement with gold-standard techniques (deviation T1: 4 ± 2%, : 4 ± 5%). The visual quality was comparable to the in vivo gold standard, despite substantially shortened scan times. Conclusion The proposed MRF-EPI method provides fast and accurate T1 and quantification. This approach offers a rapid supplement to the non-Cartesian MRF portfolio, with potentially increased usability and robustness. Magn Reson Med 78:1724-1733, 2017. © 2016 International Society for Magnetic Resonance in Medicine.